Peran Psikologi dalam Pendidikan Islam - Ratna Jauhara Karimah Elrohman; Siti Rohimah (TSAQOFAH, 2026)
Islamic education is not only oriented toward the transfer of knowledge but also toward the comprehensive formation of students’ character, morality, and spirituality. Psychology has a strategic role as a foundation for understanding students’ characteristics, needs, and development in the context of Islamic education. This article aims to examine the basic concepts of psychology from the perspective of Islamic education, the role of psychology in understanding students, the integration of psychology with Islamic values, its contribution to character formation, and its implementation in the learning process. This study uses a library research method with a descriptive-analytical approach. The results of the study show that the integration of psychology with Islamic values can create learning that is humanistic, oriented toward the formation of moral character, and balances students’ intellectual, emotional, and spiritual intelligence. The implementation of psychology in Islamic education can be carried out through adaptive learning methods, strengthening the role of teachers as mentors, and comprehensive evaluation that considers students’ developmental aspects. The conclusion of this study affirms that psychology plays an important role in strengthening Islamic education that is holistic, humanistic, and oriented toward the formation of students’ complete personality. The implications of this study indicate that the application of psychology in Islamic education can improve the quality of learning while supporting character formation and the achievement of the goals of Islamic education in forming insan kamil.